Minimization of activated sludge production by chemical uncoupler, 3,3,4,5-tetrachlorosalicylanilide - Seah, Siew Ying. (2009)
Activated sludge process is one of the most common biological processes in wastewater treatment plants worldwide. Due to its contribution to higher operating cost, excessive sludge produced in the activated sludge treatment process is a vital problem that needs to be solved. This report aims to describe the effect of fixed metabolic uncoupler concentration of varying initial biomass concentrations on reduced sludge growth in activated sludge batch culture. 3,3,4,5- tetrachlorosalicylanilide (TCS) was chosen as the uncoupler to carry out the batch tests. Sludge growth, organic removal efficiency, pH, microbial morphology and particle size were analyzed in relation to the batch experiments.